2021
DOI: 10.1007/s00127-021-02084-y
|View full text |Cite|
|
Sign up to set email alerts
|

Supporting independence at home for people living with dementia: a qualitative ethnographic study of homecare

Abstract: Purpose The aim of this ethnographic study was to investigate how homecare workers support or inhibit independence in people living with dementia. Methods We undertook 100 h of participant observations with homecare workers ( n = 16) supporting people living with dementia ( n = 17); and 82 qualitative interviews with people living with dementia ( n = 11), family carers ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…A particular challenge is to develop implementable and sustainable training models, in a setting where staff turnover is high, funding‐limited, time‐pressured (Leverton, 2020 ; Leverton et al., 2021 ) and workloads heavy (Su et al., 2021 ). Participants reflected on how these barriers could be overcome with greater organisational support, for example, through the allocation of protected time for training by employers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular challenge is to develop implementable and sustainable training models, in a setting where staff turnover is high, funding‐limited, time‐pressured (Leverton, 2020 ; Leverton et al., 2021 ) and workloads heavy (Su et al., 2021 ). Participants reflected on how these barriers could be overcome with greater organisational support, for example, through the allocation of protected time for training by employers.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention focuses on peer learning and sharing of experiences, acknowledging and drawing on the homecare workers’ different experiences, and levels of training. We co‐designed the NIDUS‐professional training and support intervention in workshops, with people living with dementia, family carers, homecare workers and managers and health practitioners, using existing interventions (Kales et al., 2015 ; Livingston et al., 2019 ; Low et al., 2015 ; Polacsek et al., 2020 ), our ethnographic studies (Leverton, 2020 ; Leverton et al, 2021 ) and lived experience of co‐designers.…”
Section: Methodsmentioning
confidence: 99%
“…Working in clients’ homes, as opposed to hospital or residential settings, may neutralise power dynamics and allow for greater autonomy and opportunities for informal care and relationship development ( Bolton & Wibberley, 2014 ); there may be scope within training to consider and reflect on the impact of providing care in clients’ homes. The home as a site of care is complex and warrants further attention ( Leverton et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by London (Camden and King's Cross) National Research Ethics Service (NRES) (reference: 17/LO/1713). Full details of procedures are reported elsewhere (Leverton et al, 2021a, 2021b). We undertook a secondary qualitative analysis of the ethnographic data derived from this earlier study, alongside an analysis of care plans for the clients observed, collected during the original study but not previously analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Home‐care support for dementia that incorporates person‐centred approaches is considered the ‘Gold standard’ (Love & Femia, 2015) with the focus on the individuality of the person and their interactions and relationships with others (Hoel et al., 2021; Kitwood, 1997). Home‐care workers are well placed to promote person‐centred care, although they often feel unsupported to carry out their roles effectively (Cooper et al., 2017; Leverton et al, 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%